Recycling of copper tailings as an additive in cement mortars - Onuaguluchi, Obinna; Eren, Özgür (Elsevier, 2012)
Increasing demands for copper and copper allied products have made the processing of low grade ores with high volume waste output unavoidable. Presently, billions of tons of copper tailings can be found in major copper producing countries. The impact of copper tailings at 0%, 5% and 10% addition level by mass of cement on the fresh and hardened properties of mortars were determined. Results showed that dry copper tailings affect mixture consistency negatively. However, the use of pre-wetted tailings reduced this drawback. Copper tailings blended mortars showed higher strength and abrasion resistance. Similarly, rate of water absorption, acid and chloride resistance higher than those of the control mixture were observed. The use of pre-wetted tailings at 5% addition level seems to be the best reuse approach.
DESCRIPTION: Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI (with DOI:10.1016/j.conbuildmat.2012.08.009) and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Copper tailings; mortar; Consistency; mechanical strength; Water absorption; Durability